A comparison of two attachment measures in relation to personality factors and facets. (1st July 2017) - Both, Lilly E.; Best, Lisa A.
Abstract: There is a large body of literature on attachment styles and personality traits. The purpose of this study was to compare two commonly used instruments of attachment that measure secure, fearful, dismissing, and preoccupied styles. Furthermore, we sought to determine which personality factors and facets were common on both of the attachment measures. Overall, 273 undergraduates completed a demographic measure, two attachment scales (RQ and RSQ), and the NEO-PI-R to measure personality. We found high concordance between the NEO-PI-R factors and facets that predicted RSQ and RQ attachment. On both measures of attachment, a secure style was associated with lower neuroticism and higher extraversion. Fearful attachment was consistently predicted by being female, having higher neuroticism (specifically depression) as well as lower extraversion and agreeableness (specifically trust). Individuals scoring higher on preoccupied attachment had higher neuroticism (specifically depression) and lower agreeableness. Finally, individuals scoring higher on dismissing attachment had lower trust. These results confirm Griffin and Bartholemew's (1994) conceptualization of attachment as falling on the dimensions of anxiety and avoidance. Individuals with higher anxiety had higher neuroticism and lower agreeableness and those with higher avoidance had lower levels of trust. Highlights: First study of the relation between the NEO-PI-R and categorical attachment styles Consistent relation between NEO-PI-R and attachment scales (RQ and RSQ) Although they measure the same concept, RSQ superior for facet level analyses Three insecure styles were related to higher depression and/or lower trust. Low trust = negative view of others and high depression = negative view of self